The solution to the differential x 2 d x 2 d 2 y − x d x d y + 2 y = 0 , where y ( 1 ) = 2 3 , y ′ ( 1 ) = 2 can be expressed as the the curve y = f ( x ) .
The area of the above curve y = f ( x ) from x = 1 to x = e 2 π can be expressed as b a ∗ ( e c π − a ) , where a , b , and c are coprime positive integers.
Find: a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Trying a solution of the form y = x m works if m ( m − 1 ) − m + 2 = 0 So that m = 1 ± i . The initial conditions give the solution y = 4 1 ( 3 − i ) x 1 + i + 4 1 ( 3 − i ) x 1 − i So the desired integral is [ 4 ( 2 + i ) 3 − i x 2 + i + 4 ( 2 − i ) 3 + i x 2 − i ] 1 e 2 π = 2 1 ( e 4 π − 1 ) Making the answer 7 .
You know you can avoid cumbersome steps by reducing the area expression by using given data itself: (3d/dx(xy) − d/dx(x^2(dy/dx)))/5)= \int_mathrm{y}\,\mathrm{d}x
Problem Loading...
Note Loading...
Set Loading...
To avoid using a power series solution we reduce x 2 d x 2 d 2 y − x d x d y + 2 y = 0 to a second order differential with constant coefficients by letting
z = ln ( x ) ⟹ d x d y = d z d y ∗ x 1
and,
d x 2 d 2 y = d x d ( d z d y ∗ x 1 ) = d z d y ( − x 2 1 ) + x 1 d x d ( d z d y ) = x 2 − 1 d z d y + x 1 d z d ( d z d y ) x 1 =
x 2 1 d z 2 d 2 y − x 2 1 d z d y
Replacing d x d y and d x 2 d 2 y in the differential above we obtain:
d z 2 d 2 y − 2 d z d y + 2 y = 0
Assuming your familiar with solving second order differential equations with constant coefficients we obtain:
m 2 − 2 m + 2 = 0 ⟹ m 1 , m 2 = 1 ± i ⟹ y ( z ) = e z ∗ ( c 1 ∗ c o s ( z ) + c 2 ∗ s i n ( z ) )
z = ln ( x ) ⟹ y ( x ) = x ∗ ( c 1 ∗ c o s ( ln ( x ) ) + c 2 ∗ s i n ( ln ( x ) ) )
and,
d x d y = ( c 2 + c 1 ) ∗ c o s ( ln ( x ) ) + ( c 2 − c 1 ) ∗ s i n ( ln ( x ) )
Using the initial conditions y ( 1 ) = 2 3 , y ′ ( 1 ) = 2 we obtain c 1 = c 2 = 1 ⟹
y ( x ) = x ∗ ( 2 3 ∗ c o s ( ln ( x ) ) + 2 1 ∗ s i n ( ln ( x ) ) )
The area A = ∫ 1 e 2 π x ∗ ( 2 3 c o s ( ln ( x ) ) + 2 1 s i n ( ln ( x ) ) ) d x
For ∫ s i n ( ln ( x ) ) d x
Let u = s i n ( ln ( x ) ) , d v = d x ⟹ d u = x 1 c o s ( ln ( x ) ) , a n d v = x ⟹
∫ s i n ( ln ( x ) ) d x = x ∗ s i n ( ln ( x ) ) − ∫ c o s ( ln ( x ) ) d x
Let u = c o s ( ln ( x ) ) , d v = d x ⟹ d u = − x 1 s i n ( ln ( x ) ) , a n d v = x ⟹
∫ s i n ( ln ( x ) ) d x = x ∗ s i n ( ln ( x ) ) − x ∗ c o s ( ln ( x ) ) − ∫ s i n ( ln ( x ) ) d x ⟹
2 ∗ ∫ s i n ( ln ( x ) ) d x = x ∗ ( s i n ( ln ( x ) ) − c o s ( ln ( x ) ) ) ⟹
∫ s i n ( ln ( x ) ) d x = 2 x ∗ ( s i n ( ln ( x ) ) − c o s ( ln ( x ) ) )
For ∫ c o s ( ln ( x ) ) d x
Let u = c o s ( ln ( x ) ) , d v = d x ⟹ d u = − x 1 s i n ( ln ( x ) ) , a n d v = x ⟹
∫ c o s ( ln ( x ) ) d x = x ∗ c o s ( ln ( x ) ) + ∫ s i n ( ln ( x ) ) d x = 2 x ∗ ( s i n ( ln ( x ) ) + c o s ( ln ( x ) ) ) ⟹
∫ s i n ( ln ( x ) ) + c o s ( ln ( x ) ) d x = x ∗ s i n ( ln ( x ) )
For ∫ x ∗ ( s i n ( ln ( x ) ) + c o s ( ln ( x ) ) ) d x
Let u = x , d v = s i n ( ln ( x ) ) + c o s ( ln ( x ) ) d x ⟹ d u = d x a n d v = x ∗ s i n ( l n ( x ) ) ⟹
∫ x ∗ ( s i n ( ln ( x ) ) + c o s ( ln ( x ) ) ) d x = x 2 ∗ s i n ( ln ( x ) ) − ∫ x ∗ s i n ( ln ( x ) ) d x
Let u = x , d v = s i n ( ln ( x ) ) d x ⟹ d u = d x a n d v = 2 x ∗ ( s i n ( l n ( x ) ) − c o s ( ln ( x ) ) ) ⟹
∫ x ∗ s i n ( ln ( x ) ) d x + ∫ x ∗ c o s ( ln ( x ) ) d x =
x 2 ∗ s i n ( ln ( x ) ) − ( 2 x 2 ∗ ( s i n ( ln ( x ) ) − c o s ( ln ( x ) ) ) + 2 1 ∗ ∫ x ∗ s i n ( ln ( x ) ) d x − 2 1 ∗ ∫ x ∗ c o s ( ln ( x ) ) d x
⟹
∫ 2 3 ∗ x ∗ c o s ( ln ( x ) ) + 2 1 ∗ x ∗ s i n ( ln ( x ) ) d x =
2 x 2 ∗ ( s i n ( ln ( x ) ) + c o s ( ln ( x ) ) )
∴ the area A = 2 x 2 ∗ ( s i n ( ln ( x ) ) + c o s ( ln ( x ) ) ) ∣ 1 e 2 π =
2 1 ∗ ( e 4 π − 1 ) = b a ∗ ( e c π − a ) ⟹
a + b + c = 7 .